A Generalization of the Pasadena Puzzle. (December 2013) - Peterson, Martin
Abstract By generalizing the Pasadena puzzle introduced by Nover and Hájek (2004) we show that the sum total of value produced by an act can be made to converge to any real number by applying the Riemann rearrangement theorem, even if the scenario faced by the decision maker is non‐probabilistic and fully predictable. A wide range of solutions put forward in the literature for solving the original puzzle cannot solve this generalized version of the Pasadena puzzle.